LasR-regulated proteases in acute vs. chronic lung infection: a double-edged sword - Lisa C. Hennemann; Dao Nguyen (Microbial Cell)
Pseudomonas aeruginosa is a gram-negative opportunistic pathogen capable of causing both acute and chronic infections, particularly in individuals with compromised host defenses. The quorum sensing transcriptional activator LasR is widely recognized for its role in regulating the expression of acute virulence factors, notably several secreted proteases which cause direct host damage and subvert host immunity in acute infections. Paradoxically, lung infections caused by LasR-deficient variants, which are found in at least a third of cystic fibrosis (CF) patients with chronic P. aeruginosa infections, are associated with accelerated lung disease and increased markers of inflammation compared to infections caused by strains with a functional LasR system. While the loss of LasR function often (although not always) results in impaired production of LasR-controlled acute virulence factors, the implication of this pathoadaptation on host-pathogen interactions and chronic disease pathology is less well recognized. We recently observed that loss of LasR function in lasR variants, which results in impaired secreted protease production, led to increased expression of the membrane-bound surface adhesion molecule mICAM-1 in the airway epithelium, and increased neutrophilic inflammation. Specifically, human airway epithelial cells stimulated with lasR variants had higher mICAM-1 expression and greater neutrophil binding in vitro compared to stimulation with wild-type P. aeruginosa. In a subacute non-lethal P. aeruginosa lung infection model, lasR variant infection also induced higher mICAM-1 expression in the murine airway epithelium and was associated with increased neutrophilic pulmonary inflammation in vivo. Here, we discuss how (loss of) LasR function and LasR-regulated proteases affect host immunity, inflammation and tissue pathology in acute vs. chronic P. aeruginosa lung infection.